Adaptation strategies to climate change and impacts on household income and food security: evidence from Sahelian region of Niger - Zakari, S.; Ibro, G.; Moussa, B.; Abdoulaye, Tahirou (MDPI, 2022)
Sahelian countries, particularly Niger, are more vulnerable to climate change due to the high dependence of most of their populations on rain-fed agriculture and limited capacities to respond to climate variability and change. This paper examines the factors influencing climate change adaptation strategies and the impacts on household income and food security in rural Niger. For this purpose, we collected data from 1783 valid rural households in four main agricultural regions of Niger. The results showed that crop diversification (72.74%), income diversification (67.97%) and changing planting times (55%) are the main adaptation strategies adopted by households. The majority of respondents had noticed changes in rain patterns (93.21%), in the amount of rain (91.25%) and in the intensity of rain (81.82%) during the last five years. We categorized these adaptation strategies into six major groups namely climate-resilient crop varieties, improved agronomic practices, irrigation and water conservation practices, crop diversification, income diversification, and agroforestry. We ran logit regression to identify the determinants of each individual group. The results show mixed effects of independent variables on these categories of adaptation strategies. Using matching techniques, we found adaptation strategies have positive and significant impact on both household income and food security. The farmers who adopt climate change adaptation strategies are more likely to increase household income by 7721.526 FCFA compared to those households with zero adaptation strategies. Similarly, the adapters have 7% to 9% more chance to be food secure compared to those who did not adopt strategies. These results suggest that strengthening the awareness of the effects of climate change on farmers and the choice of appropriate adaptation strategies are necessary to enhance household resilience. Strengthening institutional factors such as access to credit and market, extension services, and using drought-resilient crop varieties would surely improve agricultural production.